ECOLOGICAL EDUCATION AS THE BASIS OF SUSTAINABLE DEVELOPMENT (ON THE EXAMPLE OF SECONDARY SCHOOLS OF KIROVSKI DISTRICT OF THE CITY OF MAKHACHKALA, REPUBLIC OF DAGHESTAN) - Gayirbeg M. Abdurakhmanov; Ella Z. Davudova; Muslimat A. Aliverdieva (Юг России: экология, развитие, 2017)
Abstract. Aim. The aim of the study is to analyze and evaluate the current state of ecological education on the example of general education institutions of the Kirovski district of Makhachkala. Methods. The materials for the research were the results of the anonymous questionnaire survey of schoolchildren of 5-11 grades (secondary schools №21 and 3) The questionnaire was compiled on the basis of the Institute of Ecology and Sustainable Development of the Dagestan State University. The statistical processing of the survey data was carried out using an Excel software package. Findings. The result of the conducted studies revealed the average level of the current state of the ecological education. Of the 141 respondents, (school №21) 51% answered correctly the question: "What is ecology?", 80% of schoolchildren of 5-8 grades apply their knowledge of ecology in their everyday life. Whereas of the 139 students surveyed (school №3) 67% of the respondents correctly answered the same question. When studying ecology, 53% of schoolchildren noted that more and more plants and animals die every year. Conclusion. The analysis of the studies shows the need to improve the level of environmental education and ecological culture in the general educational institutions of the Republic of Dagestan for more in-depth development of environmental knowledge, their application in practice with a view to improving the quality of life and addressing the major environmental problems of our time.